2018
DOI: 10.1097/ico.0000000000001727
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Interface Keratitis After Descemet Membrane Endothelial Keratoplasty

Abstract: Fungal IK is a rare complication after DMEK. Based on our experience, we believe that treatment of early fungal IK with aggressive presentation should include both immediate graft exchange and intracameral application of voriconazole and amphotericin, in addition to topical and systemic antifungal treatment. Graft exchange seems not to be mandatory in late infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
0
37
1
2
Order By: Relevance
“…On the other hand, there have not been large series describing the rate of microbial keratitis following EK. Several case reports and case series have documented microbial keratitis of the host stroma, the graft–host interface and the graft after EK, with donor to host transmission of infection in the majority of cases (Sharma et al 2011; Augustin et al 2018; McElnea et al 2018; Fontana et al 2019). A study by Quilendrino et al (2017) identified a rate of 0.4% for the development of microbial keratitis after DMEK, which was lower than our rate of 1.3% after EK.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have not been large series describing the rate of microbial keratitis following EK. Several case reports and case series have documented microbial keratitis of the host stroma, the graft–host interface and the graft after EK, with donor to host transmission of infection in the majority of cases (Sharma et al 2011; Augustin et al 2018; McElnea et al 2018; Fontana et al 2019). A study by Quilendrino et al (2017) identified a rate of 0.4% for the development of microbial keratitis after DMEK, which was lower than our rate of 1.3% after EK.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial and fungal infections appear to be equal in prevalence [2]. A retrospective case series of 3950 eyes which underwent DMEK reported early and late fungal interface keratitis in 6 eyes (0.15 %) [5]. In another retrospective study of 500 eyes of 393 patients, unspecified microbial keratitis was documented in 2 eyes (0.4 %) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Fungi, when isolated from donor corneal rims, have more risk to lead a clinical infection than bacteria [ 11 ]. Thus, the culture of the donor corneal rim (special fungal culture) in cases of lamellar or endothelial keratoplasty could allow for an early detection and treatment [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%